Effect of Sulfurization Time on Properties of CZTS Thin Films by Solid-state Sulfurization - CAO Zhong-ming; YANG Yuan-zheng; XU Jia-xiong; XIE Zhi-wei (Cailiao gongcheng, 2016)
Cu2ZnSnS4 (CZTS) thin films were prepared by solid-state sulfurizing Cu-Zn-Sn(CZT) metallic precursors. The effect of sulfurization time on phases, chemical composition, surface morphology and optical properties was investigated by X-ray diffraction (XRD), Raman spectrum, energy dispersive of X-ray (EDS), scanning electron microscope (SEM) and UV-Vis, respectively. The results show that with the sulfurization time and content of Cu increase, Zn particularly decreases. The films that sulfurized over 40min occur with impurities like SnS, Sn2S3 and Cu2SnS3, which lead smaller optical band gap. When the sulfurization time is 20min, the sample is single phase CZTS thin film, which surface is uniform and even, Cu-poor and Sn-rich. The absorption coefficient is over 104cm-1. The band gap energy is estimated 1.56eV.